2023
DOI: 10.1002/wat2.1640
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of household water treatment in Southeast Asian countries

Abstract: Worldwide, an average gap of 32% was observed between urban and rural populations in terms of access to safe drinking water. Worryingly, 50% of the Southeast Asia population resides in rural areas, making the region highly vulnerable to threats from not having access to safe drinking water. The sparse population density and infrastructural complexities in rural areas have made centralized water treatment systems very challenging in terms of implementation and significantly increased cost. Hence, adopting a hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Based on the water quality status report in the 2020 statistical report on water quality, air and land cover from the Directorate General of Pollution Control and Environmental Damage, it is known that the status of water quality in the Wai Batu Merah Watershed for 2016 -2020 is in a heavily polluted condition (Lawrencia et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the water quality status report in the 2020 statistical report on water quality, air and land cover from the Directorate General of Pollution Control and Environmental Damage, it is known that the status of water quality in the Wai Batu Merah Watershed for 2016 -2020 is in a heavily polluted condition (Lawrencia et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pollution exacerbates the water quality deterioration, affecting industrial production and residents' lives [3,4]. Due to issues like water source and supply system pollution [5][6][7], research has shown that only 11% of the drinking water in China meets the requirements specified by the Chinese Standard for Drinking Water Quality (GB 5749-2022) [8][9][10]. As affirmed in the Universal Declaration of Human Rights, the right to an adequate standard of living includes ensuring water safety and quality.…”
Section: Introductionmentioning
confidence: 99%